Proton conductive polyoxoniobate frameworks constructed from nanoscale Nb68O200 cages. Issue 38 (13th April 2021) - Lin, Yu-Diao; Zhu, Zeng-Kui; Ge, Rui; Yu, Hao; Li, Zhong; Sun, Cai; Sun, Yan-Qiong; Li, Xin-Xiong; Zheng, Shou-Tian
Abstract : Nanoscale Nb68 O200 cages have been successfully employed as flexible and stable secondary building units to combine with bridging copper–amine complexes to construct two proton conductive polyoxoniobate frameworks, demonstrating a promising strategy for making new porous materials. Abstract : Nanoscale Nb68 O200 cages have been successfully employed as flexible and stable secondary building units to combine with bridging copper–amine complexes to construct two proton conductive polyoxoniobate frameworks, demonstrating a promising strategy for making new porous materials.